1989
DOI: 10.1113/jphysiol.1989.sp017650
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of motor unit firing during different respiratory and postural tasks in human sternocleidomastoid muscle.

Abstract: SUMMARY1. Motor unit firing has been studied in human sternocleidomastoid muscle. 2. Two needle electrodes were inserted into the muscle and the activity of pairs of motor units recorded during (a) reflex hypercapnic obstructed breathing, (b) eucapnic voluntary copying of (a) against the same inspiratory resistance and (c) eucapnic voluntary copying of (a) without any resistance, accompanied by isometric neck rotation.3. Cross-correlation histograms of the firing of unit pairs showed a clear central peak, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 30 publications
3
33
0
2
Order By: Relevance
“…Earlier studies have shown that the strength of short-term synchrony can change with different motor tasks. Adams, Datta & Guz (1989) compared synchronization in the same pairs of sternocleidomastoid motor units in conscious humans during reflex hypercapnic breathing, obstructed voluntary breathing, and unresisted isometric neck rotation. The strength of synchronization was strongest during voluntary breathing, suggesting that different pathways to motoneurones are utilized for reflexly driven compared with voluntary breathing.…”
Section: Short-term Synchronymentioning
confidence: 99%
“…Earlier studies have shown that the strength of short-term synchrony can change with different motor tasks. Adams, Datta & Guz (1989) compared synchronization in the same pairs of sternocleidomastoid motor units in conscious humans during reflex hypercapnic breathing, obstructed voluntary breathing, and unresisted isometric neck rotation. The strength of synchronization was strongest during voluntary breathing, suggesting that different pathways to motoneurones are utilized for reflexly driven compared with voluntary breathing.…”
Section: Short-term Synchronymentioning
confidence: 99%
“…In the present study we have turned our attention to the central mechanisms responsible for the generation of synchronization in terms of the organization of motoneurone synaptic input. The recording of short-term synchronization of cat intercostal motoneurones during normal respiration by Sears & Stagg (1976) and the careful analysis in terms of the underlying synaptic events (Tuck, 1977;Kirkwood & Sears, 1978;Kirkwood, Sears, Stagg & Westgaard, 1982 b) provides a sound basis for this approach and provides the investigator with a potentially powerful tool for the study of central synaptic organization in man in health and disease (Kirkwood, Sears & Westgaard, 1984;Datta et al 1985a, b;Davey, Ellaway & Friendland, 1986;Adams, Datta & Guz, 1989).…”
Section: Strength Of Synchronization and Recruitment Thresholdmentioning
confidence: 99%
“…Neurophysiological and neuroanatomical studies in the cat have shown that the respiratory motoneurone pools in the spinal cord receive direct projections from the cerebral cortex (Aminoff & Sears, 1971;Lipski, Bektas & Porter, 1986; Rickard-Bell, Tork & Bystrzycka, 1986) as well as from the respiratory pattern generators in the brain stem (Merrill, 1971;Kirkwood & Sears, 1973;Cohen, Piercy, Gootman & Wolotsky, 1974;Hilaire & Monteau, 1976;Rickard-Bell, Bystrzycka & Nail, 1985;Davies, Kirkwood & Sears, 1985;Duffin & Lipski, 1987). Electrical stimulation of the motor cortex in human subjects has revealed that many respiratory muscles receive a powerful corticospinal projection (Gandevia & Rothwell, 1987;Gandevia & Plassman, 1988;Plassman & Gandevia, 1989; see also Gandevia, McKenzie & Plassman, 1990), and a recent study of motor unit synchronization suggests that the human sternomastoid muscle receives a corticospinal drive during voluntary respiration (Adams, Datta & Guz, 1989). In addition, the human somatosensory cortex receives a projection from respiratory muscles (Gandevia & Macefield, 1989).…”
Section: Introductionmentioning
confidence: 99%